GROWTH RESPONSE AND PRODUCTION OF ONION CROPS RED (Allium ascalonicum L.) ON BIOCHAR AND ECOENZYME ADMINISTRATION - Dara Jelita Br Siregar; Najla Lubis; Armaniar (RADJA PUBLIKA, 2024)
Shallots (Allium ascalonicum L.) are horticultural plants that can be used as raw materials for the food seasoning and pharmaceutical industries. People highly appreciate their unique flavor and aroma. In addition, shallots contain minerals, potassium, phosphorus, and vitamins B and C. This research was conducted to determine the effect of biochar and ecoenzymatic treatments on the growth response and production of shallots (Allium ascalonicum L.). The research method used a Factorial Randomized Block Design (RAK) with two treatment factors. The first factor was biochar application with 4 levels: A0 = control, A1 = 650 grams/plot, A2 = 750 grams/plot, A3 = 850 grams/plot. The second factor was ecoenzymatic application with 3 levels: B = control, B1 = 500 ml/plot, B2 = 1000 ml/plot. This resulted in 12 treatment combinations and 3 replications. The observed parameters were plant height (cm), number of leaves (sheets), number of offsets per plot (bulbs), fresh bulb weight per plot (g), dry bulb weight per sample (g), and dry bulb weight per plot (g). The results showed that biochar and ecoenzymatic treatments had a significant effect on plant height (cm), number of leaves (sheets), number of offsets per plot (bulbs), and dry bulb weight per sample (g). However, these treatments did not significantly affect the fresh bulb weight per plot and dry bulb weight per plot (g).